Competitiveness as an economic category (Journal of Economic Research & Business Administration, 2016)
In the context of globalization, increasing international competition, the competitiveness of the global economic crisis is becoming a major factor in ensuring the effective functioning and sustainable development of economic entities. The article discusses the concept of competitiveness as an economic category. «Competitiveness of the organization» The analysis of the definition. Also identified the main characteristics of the inherent competitiveness of the organization. Competitiveness is viewed as a multilevel category. Disadvantages of existing definitions of the concept of competitiveness, and based on their formulated a new definition. The article discusses some aspects of the company’s competitive research, which arise from the ambiguous interpretation of its conceptual apparatus and methods of assessment.
Keywords: "competitiveness of the goods; competitiveness of the organization; evaluation of the competitiveness of the organization. "